Melanopsin-Based Brightness Discrimination in Mice and Humans - Brown, Timothy M.; Tsujimura, Sei-ichi; Allen, Annette E.; Wynne, Jonathan; Bedford, Robert; Vickery, Graham; Vugler, Anthony; Lucas, Robert J. (Current biology, 2012)
Photoreception in the mammalian retina is not restricted to rods and cones but extends to a small number of intrinsically photoreceptive retinal ganglion cells (ipRGCs), expressing the photopigment melanopsin [1–4]. ipRGCs are known to support various accessory visual functions including circadian photoentrainment and pupillary reflexes. However, despite anatomical and physiological evidence that they contribute to the thalamocortical visual projection [5–7], no aspect of visual discrimination has been shown to rely upon ipRGCs. Based on their currently known roles, we hypothesized that ipRGCs may contribute to distinguishing brightness. This percept is related to an object's luminance—a photometric measure of light intensity relevant for cone photoreceptors. However, the perceived brightness of different sources is not always predicted by their respective luminance [8–12]. Here, we used parallel behavioral and electrophysiological experiments to first show that melanopsin contributes to brightness discrimination in both retinally degenerate and fully sighted mice. We continued to use comparable paradigms in psychophysical experiments to provide evidence for a similar role in healthy human subjects. These data represent the first direct evidence that an aspect of visual discrimination in normally sighted subjects can be supported by inner retinal photoreceptors. ► Melanopsin photoreception can be selectively modulated in an intact retina ► Melanopsin supports brightness discrimination in retinal degenerate and intact mice ► Melanopsin activation induces brightness percepts in healthy humans